KAJIAN KEMANTAPAN AGREGAT TANAH PADA BERBAGAI TUTUPAN LAHAN DI LERENG BARAT GUNUNG ARJUNA - Lutfiana Hanifah; Endang Listyarini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The land use condition in Sumber Brantas Village, Batu City is 25.66% not compatible to the land capability class, while the land use condition based on the regional spatial plan there is an increase in land use by 32.05%. Land use conversion at Batu City in 2008 - 2015 reduced 748.06 ha of forest area in line with an increase in dryland area of 565.18 ha; and the increase of garden area by 329.84 ha. Transfer of land functions results in changes in land cover and causes a decrease in the potential of the actual forest function. A study related to the physical properties of the soil in Sumber Brantas Village is thus needed to obtain data on current soil conditions. This study was conducted to analyze the effect of differences in land cover and soil depth on aggregate stability and its correlation with other soil properties on the western slope of Mount Arjuna. Soil sampling was carried out on four types of land cover, i.e. horticulture, forest, shrub, and grassland at depths of 0-20 cm, 20-40 cm, and 40-60 cm with three replications for each treatment. The results showed that the type of land cover affected the soil aggregate stability, while the depth of the soil did not affect the soil aggregate stability. Organic matter influenced the value of aggregate stability with the R2 value of 0.87. Clay particles affected aggregate stability by 0.56. Aggregate stability affected soil porosity, soil macropores, and soil hydraulic conductivity with the R2 values of 0.76, 0.53, and 0.42, respectively.